CREB-binding protein, p300, butyrate, and Wnt signaling in colorectal cancer - Bordonaro, Michael (World J Gastroenterol, 2015)
This paper reviews the distinctive roles played by the transcriptional coactivators CREB-binding protein (CBP) and p300 in Wnt/β-catenin signaling and cell physiology in colorectal cancer (CRC). Specifically, we focus on the effects of CBP- and p300-mediated Wnt activity on (1) neoplastic progression; (2) the activities of butyrate, a breakdown product of dietary fiber, on cell signaling and colonic cell physiology; (3) the development of resistance to histone deacetylase inhibitors (HDACis), including butyrate and synthetic HDACis, in colonic cells; and (4) the physiology and number of cancer stem cells. Mutations of the Wnt/β-catenin signaling pathway initiate the majority of CRC cases, and we have shown that hyperactivation of this pathway by butyrate and other HDACis promotes CRC cell apoptosis. This activity by butyrate may in part explain the preventive action of fiber against CRC. However, individuals with a high-fiber diet may still develop neoplasia; therefore, resistance to the chemopreventive action of butyrate likely contributes to CRC. CBP or p300 may modify the ability of butyrate to influence colonic cell physiology since the two transcriptional coactivators affect Wnt signaling, and likely, its hyperactivation by butyrate. Also, CBP and p300 likely affect colonic tumorigenesis, as well as stem cell pluripotency. Improvement of CRC prevention and therapy requires a better understanding of the alterations in Wnt signaling and gene expression that underlie neoplastic progression, stem cell fate, and the development of resistance to butyrate and clinically relevant HDACis. Detailed knowledge of how CBP- and p300 modulate colonic cell physiology may lead to new approaches for anti-CRC prevention and therapeutics, particularly with respect to combinatorial therapy of CBP/p300 inhibitors with HDACis.